Critiquing the teaching and learning of English in Chile
1 online resource (xxi, 229 pages)
Keywords: "This edited volume critiques the hegemonic values and practices that have shaped the contemporary condition of English language education in Chile, offering a space for a transformative vision that prioritises pedagogical practices grounded in (g)localised methodologies and epistemologies. Providing insights into English language teacher education and the pedagogical practices that teachers enact in diverse contexts, chapters cover strategic and situated issues along with opportunities for alternative policies and pedagogical strategies, offering a critical exploration of learning materials. Motivated by the drive for transformative, context-sensitive and culturally relevant practice, contributors critically engage with the socio-cultural and socio-political context of Chilean English language researchers, offering a systematic analysis of the profound effects of entrenched neoliberal ideologies in education, as well as how these act to influence and shape teaching practices, policies, and outcomes. In highlighting the inherent limitations and inequities perpetuated by neoliberal policies, contributors offer alternative perspectives and solutions designed to promote more equitable, inclusive, and socially just second language educational practices. Providing a comprehensive examination of the intricate relationship between Chile's political history, socio-economic evolution, and the rise of English language education, this book will be of interest to scholars, researchers, and postgraduate students in the fields of applied linguistics, teaching and learning English as a foreign/second language, and initial English language teacher education. Policy makers working in ELT in the Chilean context may also find the volume of use"--